Mice Deficient in Perforin, CD4(+) T Cells, or CD28-Mediated Signaling Maintain the Typical Immunodominance Hierarchies of CD8(+) T-Cell Responses to Influenza Virus - Chen, Weisan (American Society for Microbiology, 2002)
CD8 T-cell (T(CD8+)) responses elicited by viral infection demonstrate the phenomenon of immunodominance: the numbers of T(CD8+) responding to different viral peptides vary over a wide range in a reproducible manner for individuals with the same major histocompatibility complex class I alleles. To better understand immunodominance, we examined T(CD8+) responses to multiple defined viral peptides following infection of mice with influenza virus. The immunodominance hierarchy of influenza virus-specific T(CD8+) was not greatly perturbed by the absence of either perforin or T-helper cells or by interference with B7 (CD80)-mediated signaling. These findings indicate that costimulation by antigen-presenting cells (APCs) or killing of APCs by T(CD8+) plays only a minor role in establishing the immunodominance hierarchy of antiviral T(CD8+) in this system. This points to intrinsic features of the T(CD8+) repertoire as major contributors to immunodominance.